Plant and fruit trait variations among four Capsicum species in a Caribbean germplasm collection. Issue 1 (April 2014) - Bharath, Sarah M.; Cilas, Christian; Umaharan, Pathmanathan
<x content-type="archive" xml:space="preserve">Abstract</x> Despite Capsicum's importance in the Caribbean, comprehensive diversity studies of this species in the region are limited, especially regarding its morphological variation. This study evaluated 37 traits (seedling, vegetative and reproductive) in 201 accessions among four Capsicum species. Multivariate analyses revealed that (i) 54% of the quantitative (seedling and fruit) variation and (ii) 64% of the qualitative (floral and fruit) variation were explained by the first two components. The three main clusters identified did not immediately highlight geographic and species-specific separation. However, significance testing revealed some separation based on geographic subgroups and species assignment. Most Southern Caribbean accessions were considerably similar to each other (if not identical in some cases), thus providing opportunity to identify and remove duplicates from the collection. These Southern Caribbean accessions shared their greatest similarity with Upper Amazon accessions, and least similarity with Lower Amazon accessions, suggesting movement of material primarily from the Upper Amazon into the Southern Caribbean Basin. The dominant differentiating traits displayed in these Southern Caribbean accessions are probably due to strong active selection for certain morphotypes and not to founder effects. Upper and Lower Amazon accessions were largely well differentiated from each other, highlighting key underlying genetic differences between these two populations and possible ongoing barriers to germplasm exchange. Central American, Greater Antilles/Bahamas and Guiana Shield accessions shared similarities with both the Upper and Lower Amazon populations, hinting at probable introductions from both Amazon regions. Collectively, this provides essential baseline information on the morphological (and underlying genetic) relationships among these accessions to guide future characterisation and evaluation efforts on this collection.